2020
DOI: 10.1016/j.ijcha.2020.100633
|View full text |Cite
|
Sign up to set email alerts
|

Electromechanical dissociation of left atrium in patients with Cardiac Amyloidosis by Magnetic Resonance: Prognostic and clinical correlates

Abstract: Objectives Left atrial (LA) function is an important marker of hemodynamic status in cardiac amyloidosis (CA), and its characterization may provide relevant prognostic information. We sought to assess the prevalence and prognostic impact of LA dysfunction by cardiac magnetic resonance (CMR) in patients with CA. Methods We performed CMR in 80 consecutive patients with CA, including 38 with AL (47%) and 42 with ATTR (53%). LA function was assessed by acquiring short axis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 16 publications
0
11
0
Order By: Relevance
“…However, LA size is insufficient to obtain detailed information about LA function. Several studies with STE demonstrated that LA systolic contraction, reservoir and conduit functions were impaired in cardiac amyloidosis [ 69 , 70 ]. Recently, Bandera and colleagues [ 20 ] reported substantial impairment of the three phasic functional atrial components (median reservoir strain 8.9%, conduit strain 6.5%, pump strain 4.0%) evaluated by STE.…”
Section: Left Atrial Function In Cardiac Amyloidosismentioning
confidence: 99%
“…However, LA size is insufficient to obtain detailed information about LA function. Several studies with STE demonstrated that LA systolic contraction, reservoir and conduit functions were impaired in cardiac amyloidosis [ 69 , 70 ]. Recently, Bandera and colleagues [ 20 ] reported substantial impairment of the three phasic functional atrial components (median reservoir strain 8.9%, conduit strain 6.5%, pump strain 4.0%) evaluated by STE.…”
Section: Left Atrial Function In Cardiac Amyloidosismentioning
confidence: 99%
“…Echo-speckle tracking now has an established role in the characterization of atrial function ( 13 ) and can assess the ability of the atria to expand during ventricular systole (reservoir function), the early-diastolic emptying (conduit function), the atrial shortening (atrial contraction), and—when associated with the estimation of LV pressures—the resistance to deformation of the LA (LA stiffness) ( 14 ). Preliminary findings in cardiac amyloidosis have demonstrated impaired atrial systolic contraction ( 15 ) but also loss of reservoir function, resulting in an atrium that acts merely as a conduit throughout the cardiac cycle ( 16 , 17 ). To date, only small retrospective speckle-tracking studies have been conducted in ATTR amyloidosis, and along with little in the way of histological evaluation of the atrial wall, the significance of atrial infiltration, remodeling, and dysfunction in the pathophysiology of cardiac ATTR amyloidosis is not clear.…”
mentioning
confidence: 99%
“…In this context, the detection of myocardial deformation by speckle tracking at echocardiography allows the identification of one-fifth of patients who show a severe impairment of contractility despite remaining in sinus rhythm on the electrocardiogram [ 20 ]. This condition is also known as atrial electromechanical dissociation, proven to be associated with a poor prognosis [ 9 , 21 ].…”
Section: Atrial Arrhythmiasmentioning
confidence: 99%